KAJIAN MENGENAI PEMANFAATAN PERHUTANAN SOSIAL DALAM PERDAGANGAN KARBON DI INDONESIA UNTUK MENGHADAPI PERUBAHAN IKLIM - Posma, Posma Hutasoit (Fundamental Management Journal, 2024)
Global warming and climate change have become one of the most pressing environmental issues facing global society today. Efforts to reduce greenhouse gas (GHG) emissions, especially carbon dioxide (CO2), have become the main focus in efforts to mitigate the negative impacts of climate change. One of the instruments introduced to reduce carbon emissions is carbon trading. In Indonesia, the social forestry program is an initiative that aims to empower local communities in sustainable forest management, which is closely related to the concept of carbon forests. Through community participation in social forestry programs, it is hoped that harmony can be created between the interests of nature conservation and sustainable economic development. This article aims to provide a comprehensive understanding of the concept of carbon trading, its basic principles, benefits, and implementation through social forestry in Indonesia. This research uses a literature review method to present a comprehensive overview of this topic, by combining and analyzing information from various available sources. By understanding the basic concepts of carbon trading, operational principles, and involving communities in forest management, Indonesia has great potential to reduce carbon emissions and improve the welfare of local communities while preserving tropical forests that are rich in biodiversity. Keywords: Russia-Ukraine War, Global Economy, Geopolitical Risk